Proceedings of the 4th International Symposium on Health Research (ISHR 2019) 2020
DOI: 10.2991/ahsr.k.200215.021
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activities of Ethyl Acetate Fraction From Uncaria Gambir Leaves Through the Inhibition of Edema, COX-2 and iNOS Expression

Abstract: Inflammatory is a body defense mechanism due to respond of tissue on undermine influences, either local or the one that go into the body. Inflammatory can cause various physical dysfunctions. Uncaria gambir Roxb, a high catechin content in ethyl acetate fraction, is widely used as wound healing in Indonesian culture, therefore its mechanism of anti-inflammatory action is still unknown. The objective of our study is to investigated the activity of anti-inflammatory ethyl acetate fraction of Uncaria gambir leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…To reduce the moisture content, the next step was to dry the product in an oven for a day at a temperature of 40 to 50°C. 9 Fractionation of gambir leaf extract Fractionation was carried out by macerating gambir leaf extract powder in a chromatographic column using ethyl acetate as solvent. After 24 hours, the faucet on the column was slightly opened, and the ethyl acetate fraction of gambir leaf extract was collected using an Erlenmeyer flask.…”
Section: Extraction Of Gambir Leaf Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce the moisture content, the next step was to dry the product in an oven for a day at a temperature of 40 to 50°C. 9 Fractionation of gambir leaf extract Fractionation was carried out by macerating gambir leaf extract powder in a chromatographic column using ethyl acetate as solvent. After 24 hours, the faucet on the column was slightly opened, and the ethyl acetate fraction of gambir leaf extract was collected using an Erlenmeyer flask.…”
Section: Extraction Of Gambir Leaf Extractmentioning
confidence: 99%
“…The column temperature was maintained at 30 °C with a Sunfire C18 column sized at 4.6 × 150 mm, 0.45 mL/min flow rate, a 1.0 µL injection volume, and UV detection at 280 nm using a PDA detector (Waters). 9 Preparation of standard solutions Standard stock solutions of catechin were prepared by weighing 25 mg (25,000 µg) of standard catechin and then dissolving it in mobile phase B up to 25 mL (1000 µg/mL). The standard stock solution was diluted with acetonitrile to obtain the desired serial concentrations (50, 75, 125, 150, and 200 µg/mL).…”
Section: High-performance Liquid Chromatography Conditionsmentioning
confidence: 99%
“…In 2019, Musdja et al [ 106 ] studied in vivo catechins isolated from gambir using ethyl acetate solvent with Winter’s modified paw edema method. This study reported that the best dose for inhibiting edema was 100 mg/kg BW with a concentration of 59.19%.…”
Section: Uncaria Gambir Roxb Usesmentioning
confidence: 99%
“…Gambir leaves were fractionated using ethyl acetate, methanol, and water solvents, with ethyl acetate solvents having the greatest catechin content, which exceeded 90%. 3 © 2024 the authors. This work is licensed under the Creative Commons Attribution 4.0 International License mixer (Canaan), a tableting press machine (Jen Chiang), a tableting coating machine (Hong Dau), an ultra-mixer (Turrax), a highperformance liquid chromatography (HPLC; Waters), a dissolution tester (Hanson), a hardness tester (Erweka), a friabilator (Erweka), an analytical balance (Metler Toledo), a disintegration tester (Erweka), and a climatic chamber (Memmert).…”
Section: Introductionmentioning
confidence: 99%